2017
DOI: 10.1002/1873-3468.12930
|View full text |Cite
|
Sign up to set email alerts
|

Pupylation of PafA or Pup inhibits components of the Pup‐Proteasome System

Abstract: The pupylation of cellular proteins plays a crucial role in the degradation cascade via the Pup‐Proteasome system (PPS). It is essential for the survival of Mycobacterium smegmatis under nutrient starvation and, as such, the activity of many components of the pathway is tightly regulated. Here, we show that Pup, like ubiquitin, can form polyPup chains primarily through K61 and that this form of Pup inhibits the ATPase‐mediated turnover of pupylated substrates by the 20S proteasome. Similarly, the autopupylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…Pup is in fact degraded by the proteasome, albeit at a rate much slower than expected for most proteins, based on the analysis presented here using model substrates. Our findings in this regard, relying on the M. smegmatis PPS, are consistent with a previous report showing that M. smegmatis Pup is poorly degraded by the M. smegmatis proteasome in vitro (Alhuwaider et al, 2018). At the same time, our findings are apparently less consistent with the report of full degradation of M. tuberculosis Pup by the M. tuberculosis proteasome in vitro (Striebel et al, 2010).…”
Section: Pup Lacks Favorable 20s Cp Cleavage Sitessupporting
confidence: 90%
See 2 more Smart Citations
“…Pup is in fact degraded by the proteasome, albeit at a rate much slower than expected for most proteins, based on the analysis presented here using model substrates. Our findings in this regard, relying on the M. smegmatis PPS, are consistent with a previous report showing that M. smegmatis Pup is poorly degraded by the M. smegmatis proteasome in vitro (Alhuwaider et al, 2018). At the same time, our findings are apparently less consistent with the report of full degradation of M. tuberculosis Pup by the M. tuberculosis proteasome in vitro (Striebel et al, 2010).…”
Section: Pup Lacks Favorable 20s Cp Cleavage Sitessupporting
confidence: 90%
“…The identification of Pup-derived degradation fragments in biochemical assays of proteasome activity supports this assumption (Striebel et al, 2010). At the same time, others have shown that free Pup, unlike pupylated proteins, is poorly degraded by the proteasome (Alhuwaider et al, 2018). Furthermore, in vivo studies of tagged protein degradation in M. tuberculosis and M. smegmatis suggested that Pup can escape digestion and be recycled by the depupylase activity of Dop (Cerda-Maira et al, 2010;Elharar et al, 2017).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, the bacterial proteasome is only expressed in Actinobacteria such as Mycobacteria tuberculosis ( M.tb ). In contrast to ubiquitination, substrates are tagged for degradation on lysine side chains by a ubiquitin-like protein (Pup), resulting in substrate pupylation . In contrast to the necessary requirement of polyubiquitination for substrate recognition and degradation in eukaryotes, a single Pup is considered sufficient for targeting of substrates to the bacterial proteasome.…”
Section: Prokaryotic Protein Quality Control Systemsmentioning
confidence: 99%
“…As a compromise, such proteins were instead expressed as chimeric Pup fusions that were purified and used as model substrates . Such fusion proteins were indeed recognized and degraded by the bacterial proteasome. , At the same time, the usefulness of such chimeric Pup fusions as a substitute for pupylated proteins is limited. Specifically, Pup fusions cannot undergo depupylation by Dop, since they do not present an isopeptide bond .…”
Section: Introductionmentioning
confidence: 99%